2021
DOI: 10.3390/sexes2040030
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Sexual Agency. Implications for Sexual Health Programming

Abstract: Debates on human agency, especially female and sexual agency, have permeated the social scientific literature and health educational practice for multiple decades now. This article provides a review of recent agency debates illustrating how criticisms of traditional conceptions of (sexual) agency have led to a notable diversification of the concept. A comprehensive, inclusive description of sexual agency is proposed, focusing on the navigation of goals and desires in the wider structural context, and acknowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 63 publications
0
7
0
2
Order By: Relevance
“…Multi-country investment is pertinent to identify contextually relevant and culturally sensitive interventions and programmes to enhance adolescent SRH and prevent, interrupt, and address the various barriers to accessing adolescent friendly SRH services and products. Contextual factors not only play significant roles in shaping the quality, availability, and accessibility of SRH services and programs for AGYW, but also regulates how young people make decisions or enact their agency and constructions of hope (14,17,37). For example, studies show that AGYW's ability to exercise autonomy over their bodies is constrained by traditional, cultural, and religious norms that view publicly expressing sexuality and talking about sex as taboo (38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multi-country investment is pertinent to identify contextually relevant and culturally sensitive interventions and programmes to enhance adolescent SRH and prevent, interrupt, and address the various barriers to accessing adolescent friendly SRH services and products. Contextual factors not only play significant roles in shaping the quality, availability, and accessibility of SRH services and programs for AGYW, but also regulates how young people make decisions or enact their agency and constructions of hope (14,17,37). For example, studies show that AGYW's ability to exercise autonomy over their bodies is constrained by traditional, cultural, and religious norms that view publicly expressing sexuality and talking about sex as taboo (38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…It implies a belief that the individual has the potential to direct a sequence of events that make the sum of lived experience. Pertaining to SRH, Vanwesenbeeck, and colleagues (14) uses the term sexual agency which describes young women's ability to make sexual choices, including initiating sex. Banerjee et al (13) argues that a lack of SRH knowledge and information, and limited agency to negotiate sexual encounters contribute to early and unprotected sex for youth.…”
Section: Agency Hope and Adolescent Srhmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, sexual agency has many benefits, including, but not limited to, psychological well-being [ 50 ] and promoting sexual and reproductive health [ 51 ]. Previously, sexual agency has been noted as an attribute bound by opportunities, restrictions, and privilege [ 51 ]. To increase sexual agency in LGBTQ+ people with IDD, there needs to be fewer restrictions and more access to sexual socialization opportunities, as sexual expression is not the privilege of the heterosexual cis-gender population, but everybody’s right.…”
Section: Intimate Justice Framework and Sexual Agencymentioning
confidence: 99%
“…Previous research demonstrated that overcoming traditional sex roles may contribute to young people's sexual well-being (Casique, 2019). Furthermore, researchers have recently called for gender-transformatory approaches to sexual education including (female) sexual agency (see Vanwesenbeeck et al, 2021, for a critical overview on sexual agency). Previous research also demonstrated that sexual-health interventions that addressed the issue of gender and power were more effective than interventions that did not include these issues (see Haberland, 2015, for a review).…”
Section: Novel Aspects Of the Study And Implications For Intervention...mentioning
confidence: 99%